PWE-033 Abundance of sulphate reducing bacteria in inflammatory bowel disease. (23rd September 2015) - Jia, W; Griffiths, L; Whitehead, R; Basser, S J; Dawson, C; Turner, C; Bessant, C; Fowler, D; Walton, C; Ramsden, D; Waring, R; Cole, J; et al.
Abstract : Introduction: As one of the possible causes of inflammatory bowel disease (IBD), the microbiota in the human gut has been widely studied. Sulphate-reducing bacteria (SRB) have long been considered as candidate pathogens because their metabolic product, sulphide, through its toxic properties, damages the colonic epithelium. However, no specific SRB has been identified as a pathogen to IBD, and even their abundance in the human gut remains controversial. This project compares the amount of faecal SRB in healthy subjects with that in patients either with Crohn's disease (CD) or ulcerative colitis (UC), and traces the change, if any, after treatment in each patient. Methods: Faecal samples were collected from 18 healthy subjects, 18 CD patients and 14 UC patients. CD patients were treated with elemental diet and UC patients received conventional treatment. A suspension of the faecal matter from each patient both before and after treatment was inoculated into a sulphate-rich growth medium, Postgate B. The abundance of SRB was gauged according to the amount of black precipitate (ferrous sulphide) formed by SRB. Results: Contrary to expectation 88% of healthy subjects carry SRB that produce high levels of sulphide in vitro, despite its cytotoxicity in vivo. In contrast, this carriage rate is low (45%) in CD patients at their initial presentation. After taking elemental diet, the carriage rate of active SRB did not change despite a significant fall in the total amount of gut bacteria. In UC patients, who are often characterised with mucus depletion, the carriage rate of active SRB is significantly lower (31%, p<0.05) when compared to healthy control. This finding is consistent with a previous proposal that sulphate in mucins rather than that in undigested food is the energy source for SRB. After conventional treatment, the carriage rate increased from 31% to 69%. Conclusion: In healthy subjects, SRB that produce high levels of sulphide in vitro are prevalent in the human gut but do not cause adverse effects. An impaired mucous sulphation might be associated with most of UC patients who carry low levels of active SRB.